Data for: Parascaris spp. induced surgical colic in juvenile horses – a Scandinavian perspective - Hedberg Alm, Ylva (Swedish University of Agricultural Sciences, 2026)
This data set contains retrospectively collected data from medical records of juvenile horses (< 2 years, > 1 month) that were subjected to exploratory laparotomy due to colic at six different equine hospitals in Sweden, Norway and Denmark. The time period for data collection varied between 7-15 years depending on hospital and data availability. Data collected includes date of admission, age, sex, breed, diagnosis at exploratory laparotomy, presence of Parascaris spp. and outcome. In addition, data regarding anthelmintic treatment history was included when available.

Detta dataset innehåller retrospektivt insamlad data från journaler på unga hästar (< 2 år, > 1 månad) som buköppnats vid sex olika hästkliniker Sverige, Norge och Danmark. Datainsamlingsperioden varierar mellan 7-15 år beroende på klinik och datatillgänglighet. Data som insamlats omfattar datum för ankomst till kliniken, ålder, kön och ras, diagnos vid buköppning, förekomst av spolmask samt utgång. Vidare insamlades data avseende avmaskningshistorik när denna fanns tillgänglig.
Data för: Parascaris spp. orsakad kolik hos buköppnade unga hästar - ett skandinaviskt perspektiv
Keywords: Colic; Kolik; parasitology; parasitologi; Ascariasis with intestinal complications; Spolmaskinfektion med tarmkomplikationer; Parascaris; Parascaris; horses; hästar; abdominal surgery; buköppning; Veterinary Science; Veterinärmedicin; Clinical Science; Klinisk vetenskap